Predicting Carotid Plaque Characteristics Using Quantitative Color-Coded T1-Weighted MR Plaque Imaging: Correlation with Carotid Endarterectomy Specimens - Narumi, S.; Sasaki, M.; Ohba, H.; Ogasawara, K.; Kobayashi, M.; Natori, T.; Hitomi, J.; Itagaki, H.; Takahashi, T.; Terayama, Y. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: MR plaque imaging is used to evaluate the risk of embolic complications during carotid endarterectomy and carotid artery stent placement. However, its performance for characterizing intraplaque components has varied across studies and is generally suboptimal. Hence, we correlated MR imaging results with histologic findings to determine whether a combination of high-contrast T1-weighted imaging and quantitative image analysis could readily determine plaque characteristics. MATERIALS AND METHODS: We prospectively examined 40 consecutive patients before carotid endarterectomy by using a 1.5T scanner and axial T1-weighted spin-echo images under optimized scanning conditions. The percentage areas of intraplaque fibrous tissue, lipid/necrosis, and hemorrhage were calculated automatically by using the software with previously reported cutoff values and were compared with those of the specimens. The thickness of the fibrous cap was also measured manually. RESULTS: The percentage areas of fibrous, lipid/necrotic, and hemorrhagic components were 5.7%–98.7%, 1.3%–65.7%, and 0%–82.0%, respectively, as determined by the MR images, whereas the corresponding values were 4.8%–92.3%, 7.0%–93.8%, and 0%–70.4%, respectively, as determined by histologic examination. Significant positive correlation and agreement were observed between MR images and histologic specimens (r = 0.92, 0.79, and 0.92; intraclass correlation coefficients = 0.91, 0.67, and 0.89; respectively). Thickness of the fibrous caps on MR images (0.21–0.87 mm) and in the specimens (0.14–0.83 mm) also showed positive correlation and agreement (r = 0.61, intraclass correlation coefficient = 0.59). CONCLUSIONS: Quantitative analysis of high-contrast T1-weighted images can accurately evaluate the composition of carotid plaques in carotid endarterectomy candidates. ICCintraclass correlation coefficientSEspin-echo